IMPLEMENTASI PROGRAM POLA ASUH (PARENTING) DALAM UPAYA PENCEGAHAN DAN PERCEPATAN PENURUNAN STUNTING DI KELURAHAN PANGGUNG KOTA TEGAL - Dwi Wijayanti, Sari; Puspo Priyadi, Budi; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2024)
Panggung village is the area with the most stunting cases in Tegal City that occurs because the parent’s knowledge about complience of good nutrition for children is low. Increased the parent’s knowledge in effort to prevent and reduce of stunting in Panggung Village can be implemented thru parenting program. This research aims to describe implementation of parenting program in effort to prevention and reduction of stunting in Panggung Village Tegal City and to analyze the barrier factors in implementation. This research uses a qualitative method with a descriptive approach. The results of this research showed that aims of parenting prorgam have not fully understood by kader posyandu and target group. The activities to achieve the aims of program are carried out through education activities in class of toddler’s mother, provision of PMT made from local food, Posyandu, and independent nutrition counselling. The results of the activities have not been optimal because mothers of todller and infant have not had an increase in parenting knowledge and have not been able to fully change the behaviorof mother’s todller in good care of their children. In addition, although there is a decrease in stunting cases at the level of village, it is still fluctuating. The barrier factors in the implementation of parenting program involve internal factor, namely the presence of the target group in every activity is not optimal, and external factor, namely the living environment and the economic capacity of the famil. Recomendations from this research are conducting sosialisation to kader posyandu so that they understand the parenting program, to establish the Bina Keluarga Balita, to make an intensive approach to the target group to participate in education activities, to conduct home visits to provide more routine education, and to provide material assistance for families who really need it